THE LANGUAGE IN CHINUAACHEBE'S A MAN OF THE PEOPLE - Angelika Riyandari (Soegijapranata Catholic University, 2003)
A chebe's 'A Mall of the People' as a product of post - colonial literature shows an interaction betweell imperial Cltlture and the native cultural practices especially. in terllls of language. The limitation andfailure of standard Engli h to express local experiences i.e. indigenous metaphor is shown. The emergence of new English as a result of the reconstructioll and expansion of the standard English is thus encouraged. It is resulted in the use offour different modes in the novel: standard English narration. standard English dialogue. pidgin English alld native language which reflects different attitudes implied by the speakers